Pengaruh Return On Assets, Arus Kas Bebas, Firm Size, dan Price Earnings Ratio terhadap Dividend Payout Ratio - Indah Armelia; Muhammad Jusman Syah (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This research aimed to determine empirically the influence of Return On Assets, Free Cash Flow, Firm Size and Price Earnings Ratio on Dividend Payout Ratio on consumer non-cyclicals companies listed on the IDX in 2019 – 2023. This research was conducted using secondary data such as company financial reports. Datas were collected by  purposive sampling technique. In line with that, there were 95 datas from 19 companies which consistently give dividends each year. Additionally, the research used multiple linear regression model which was tested using IBM Statistics Product and Solution (SPSS) version 26. The results of the analysis showed that Return On Assets dan Price Earnings Ratio have positive and significant effect on Dividend Payout Ratio. Free Cash Flow and Firm Size have no significant effect on Dividend Payout Ratio.